Penerapan Hak Narapidana Wanita Hamil di Lembaga Permasyarakatan: Studi Kasus di Lapas Wanita Kelas II A Tanjung Gusta Medan - Lusi Rahmadhani Efendi; Zaid Alfauza Marpaung (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
as indonesia citizens, of course we have rights that have existed since birth. Likewise for convicts who are serving their sentence in prison, women convicts should pay more attention to their rights when they are in prison because as women they have the nature to conceive, give birth and breastfeed. pregnant women in correctional institutions and how to implement the rights of pregnant women inmates in prisons. The author uses the Juridical Empirical Method in this study using a purposive sampling approach. The results of the study are that pregnant female prisoners in the class IIA female correctional facility in tanjung gusta Medan have not all of their rights have been fulfilled where there is still a lack of facilities in correctional institutions and there are no doctors who are specifically in the correctional institution.